If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + m = 4x + 3 Reorder the terms: 5 + m = 3 + 4x Solving 5 + m = 3 + 4x Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + m = 3 + -5 + 4x Combine like terms: 5 + -5 = 0 0 + m = 3 + -5 + 4x m = 3 + -5 + 4x Combine like terms: 3 + -5 = -2 m = -2 + 4x Simplifying m = -2 + 4x
| 2(4+9w)=26w | | (w+2)(2w-1)=0 | | 2*8+3*-9= | | 3.45*4-8.18= | | 8m-5=(3m+5) | | 3.45(4)-8.18(1)= | | 3+3*6+2=-17 | | 500*98+x*0=(500+x)*30 | | 6n+3-5=-1 | | 6y+814=1186 | | cos(20)=(9/x) | | 32/-7 | | 4(1/4) | | 3x+10y=-15 | | F^2-22f+72=0 | | (5-8w)(5+8w)= | | 12-9y=-5 | | -7x+6-9=29 | | -4+3=-12+17x | | 3z/10-5=8 | | 5(2b-3)=3(b+9) | | 12(12n)+n-3=396 | | 1/8-X/7=3/56 | | F^2-22f=72 | | -4(1-7z)=-29 | | 5x-2/3=-49/10 | | 15x^4-15x^3=0 | | Z/7-2=6 | | f(x)=x^4+32 | | 8(p-a)-6=2(ap-5) | | 6x+7y(2-3y)=-21 | | 24x+9=21 |